The Paradox of Rebus Sic Stantibus Principle: The Dialectic between Stability and Flexibility in Contemporary International Treaty Law - Ardiansyah, Ardiansyah; Samad, Rezki Purnama; Sutiyono, Rahmat (SIGn Jurnal Hukum, 2025)
International treaty law confronts a fundamental dialectic between the stability guaranteed by the principle of pacta sunt servanda and the demand for flexibility driven by disruptive global dynamics. The principle of rebus sic stantibus serves as a theoretical safety valve to ensure justice. In practice, however, it has become a paradox: a doctrine that is formally recognized yet rendered virtually inaccessible by highly restrictive interpretations. Through normative legal research employing statute, conceptual, and jurisprudential analysis approaches, this study examines the legal architecture and judicial practice that shape this doctrine. The analysis reveals that its codification in Article 62 of the 1969 Vienna Convention deliberately established onerous cumulative conditions. This policy is reinforced by the judicial practice of the International Court of Justice, which has consistently rejected claims of a fundamental change of circumstances in key cases. It creates a significant chasm between the doctrine’s theoretical existence as an instrument of justice and the reality of its severely limited application, establishing it as a ‘sleeping giant’ within the international legal order. This study concludes that this rigidity threatens the relevance of treaty law in responding to contemporary crises, such as systemic climate change and technological disruption. Therefore, this study recommends a renewed discourse on a more dynamic interpretation to rebalance stability with justice.